EGO DEFENSE MECHANISM OF THE MAIN CHARACTER IN NEIL GAIMAN’S THE OCEAN AT THE END OF THE LANE - Malva Adinia Azahra; Agnes Setyowati; Ni Made Widisanti (Journal Albion : Journal of English Literature, Language, and Culture, 2022)
This study analyzes the main character’s defense mechanisms when experiencing conflict in Neil Gaiman’s The Ocean at the End of the Lane. This research uses descriptive analysis method with a literary psychology approach that focuses on Sigmund Freud’s psychoanalytic theory regarding defense mechanism. The research technique is library research. The research findings reveal that the main character performs defense mechanisms such as rationalization, sublimation, denial, identification, and repression when he encounters unwanted feelings.Keywords: main character; defense mechanism; psychoanalysis; literary psychology; anxiety.